HUMAN RESOURCES OFFICE - Salsabila, Putri; Fadilasari, Nadia Sofia; Nasrun Harahap (International Journal of Multidisciplinary Reseach, 2025)
Human Resources (HR) is one of the most vital elements in carrying out various organizational activities, as it is humans who act as the main drivers of every process planning, organizing, implementation, and supervision in the work environment.This study aims to describe the definition of office HR, the roles and functions in office work, the competencies required in office HR, and the challenges faced within it. The research uses a qualitative approach with a literature review method. Data collection was conducted through literature analysis from various books and relevant journal articles. The research findings show that office HR includes all individuals working in an office environment who are responsible for various administrative, managerial, and operational tasks to support the smooth running of company or organizational activities. This concept also includes various other aspects. However, it remains aligned with Islamic principles relevant to office HR, as reflected in QS. Al-Isra' verse 36, which teaches: “And do not pursue that of which you have no knowledge. Indeed, the hearing, the sight, and the heart about all those [one] will be questioned.” Likewise, QS. An-Nahl verse 125, which emphasizes calling mankind to the way of Allah with wisdom and good instruction and arguing with them in the best manner. Truly, it is Allah who knows best who has strayed from His way, and He is most knowing of who is rightly guided. This study is highly relevant to understanding office HR, especially in helping to comprehend the concept of office human resources.